A new distinct, disjunct giant millipede of the genus Spirostreptus Brandt, 1833, from Tanzania, and a solution for orphaned Spirostreptus species (Diplopoda, Spirostreptida, Spirostreptidae) - Enghoff, Henrik (Zootaxa, 2023)
Spirostreptus digitus sp. nov. is described based on specimens from Tanzania, and the genus Spirostreptus Brandt, 1833 is discussed, as is the higher classification of the family Spirostreptidae. Gonopod illustrations of S. heros Porat, 1872, and S. tripartitus Cook & Collins, 1893, are provided for comparison with the new, morphologically very distinct species. Analocostreptus Silvestri, 1910, is suggested as the valid genus name for the species currently being placed in Spirostreptus sensu auctorum, nec Brandt, 1833, and 32 nominal species of Spirostreptus are placed in new combinations with Analocostreptus, viz., Analocostreptus amandus (Attems, 1914), comb. nov., Analocostreptus biconus (Attems, 1934), comb. nov., Analocostreptus bonifatius (Attems, 1914), comb. nov., Analocostreptus castaneus (Attems, 1934), comb. nov., Analocostreptus cornutus (Attems, 1934), comb. nov., Analocostreptus damasus (Attems, 1953), comb. nov., Analocostreptus dartevellei (Attems, 1953), comb. nov., Analocostreptus dentiger (Attems, 1953), comb. nov., Analocostreptus garambanus (Chamberlin, 1927), comb. nov., Analocostreptus gregorius (Attems, 1914), comb. nov., Analocostreptus ineptus (Kraus, 1958), comb. nov., Analocostreptus informis (Attems, 1938), comb. nov., Analocostreptus makarius (Attems, 1914), comb. nov., Analocostreptus manyemanus (Attems, 1927), comb. nov., Analocostreptus manyemanus biserialis (Attems, 1938), comb. nov., Analocostreptus medjensis (Chamberlin, 1927), comb. nov., Analocostreptus micromelas (Saussure & Zehntner, 1902), comb. nov., Analocostreptus missionarius (Attems, 1953), comb. nov., Analocostreptus montivagus (Karsch, 1881), comb. nov., Analocostreptus multisulcatus (Demange, 1957), comb. nov., Analocostreptus pancratius (Attems, 1914), comb. nov., Analocostreptus pavani (Demange, 1981), comb. nov., Analocostreptus phthisicus (Saussure & Zehntner, 1902), comb. nov., Analocostreptus pictus (Saussure & Zehntner, 1902), comb. nov., Analocostreptus rolini (Silvestri, 1897), comb. nov., Analocostreptus sculptus (Saussure & Zehntner, 1902), comb. nov., Analocostreptus semilunaris (Peters, 1855), comb. nov., Analocostreptus servatius (Attems, 1914), comb. nov., Analocostreptus tetricus (Attems, 1934), comb. nov., Analocostreptus tiburtius (Attems, 1953), comb. nov., Analocostreptus triangulicollis (Attems, 1934), comb. nov., Analocostreptus versicolor (Saussure & Zehntner, 1902), comb. nov. and Analocostreptus yambatanus (Attems, 1934), comb. nov. Illustrations of the gonopods of A. ibanda (Silvestri, 1907), type-species of Analocostreptus, are provided, and the species is recorded as new for Kenya.